SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PERDAGANGAN ORANG (Studi Beberapa Putusan Pengadilan Negeri di Indonesia) - Perdana Eliakhim Manalu; Suhaidi Suhaidi; Muhammad Hamdan; Hasim Purba (USU LAW JOURNAL, 2014)
ABSTRACT Criminal sanctions against the perpetrators of acts of trafficking in persons has been regulated in law No. 21 of 2007 about the eradication of trafficking in persons. The disparity of the overthrow of the criminal are basically starting from the sanctions contained in Act No. 21 of 2007 about the eradication of trafficking in persons which opened opportunities due to the minimum and maximum limits of awarding the penalty. The application of criminal sanctions against the perpetrators of acts of trafficking in persons based on some of the verdicts in Indonesia are based on factors that unfold in the first trial, the public prosecutor's Indictment, the two witnesses, the third the fourth accused, details wares fifth and evidence based on clauses in the legislation. Legal measures to prevent trafficking in persons, namely: the first Step to prevention, awareness-raising on the rights, the danger of sexual exploitation or trick used by traffickers. Secondly, the Measures of protection which provides protection to the victim by means of an increase in the legal network, those steps running effective if various forms of guarantee and legal mechanisms in force. Third, step up rehabilitation/restoration of the post-rescue victims from addressing the crime of trafficking, especially victims who have experienced a bad psychological impact of trauma psychology, such as fear and anxiety, prolonged low confidence, guilt.